PENERAPAN EVIDENCE BASED NURSING DENGAN INTERVENSI MASSAGE EFFLURAGE MENGGUNAKAN VIRGIN COCONUT OIL DALAM MENCEGAH LUKA TEKAN PADA PASIEN DI RUANG INTENSIVE CARE UNIT (ICU) - Rismayanti Saleha (2022)
Patients who are in critical condition can experience decreased consciousness to immobilization, all of which require them to be bed rest and are less able to change positions. Bed rest for a long time can cause pressure ulcer. Massage efflurage using virgin coconut oil can increase tissue circulation and maintain skin moisture which can be used to prevent pressure ulcer. This study aims to determine the effectiveness of massage efflurage using virgin coconut oil in preventing pressure ulcer in patients in intensive care unit. To determine the risk of pressure ulcer in patients in the intensive care unit using the Braden scale. The results of the case studies conducted showed an increase in the Braden scale score or a decrease in the risk of pressure ulcer through the application of efflurage massage using virgin coconut oil in patients in the intensive care unit with nursing intervention given for three days with a frequency of twice a day.